2021
DOI: 10.3390/molecules26040853
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Promotes Hypertrophy in Wildtype Skeletal Muscle and Reduces Muscle Necrosis and Gene Expression of Inflammatory Markers in Mdx Mice

Abstract: Duchenne muscular dystrophy (DMD) is a progressive fatal neuromuscular disorder with no cure. Therapies to restore dystrophin deficiency have been approved in some jurisdictions but long-term effectiveness is yet to be established. There is a need to develop alternative strategies to treat DMD. Resveratrol is a nutraceutical with anti-inflammatory properties. Previous studies have shown high doses (100–400 mg/kg bodyweight/day) benefit mdx mice. We treated 4-week-old mdx and wildtype mice with a lower dose of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…One of these compounds is resveratrol, a natural compound that increases SIRT1 expression which stimulates the SIRT1/PGC-1α axis in mdx mice [ 75 , 76 ]. Several studies have shown the efficacy of resveratrol treatment in ameliorating dystrophic pathology in mdx mice, showing it can improve mitophagy [ 44 , 46 ], reduce ROS levels [ 76 ], reduce inflammation [ 45 , 77 , 78 ], and increase utrophin [ 77 ] expression. One study compared the beneficial effects of resveratrol to the gold standard α-methyl prednisolone.…”
Section: Introductionmentioning
confidence: 99%
“…One of these compounds is resveratrol, a natural compound that increases SIRT1 expression which stimulates the SIRT1/PGC-1α axis in mdx mice [ 75 , 76 ]. Several studies have shown the efficacy of resveratrol treatment in ameliorating dystrophic pathology in mdx mice, showing it can improve mitophagy [ 44 , 46 ], reduce ROS levels [ 76 ], reduce inflammation [ 45 , 77 , 78 ], and increase utrophin [ 77 ] expression. One study compared the beneficial effects of resveratrol to the gold standard α-methyl prednisolone.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, administration of 0.4 g resveratrol/kg to mdx mice prevent mitochondria accumulation and reduced ROS levels [ 212 , 213 ]. This polyphenol further promotes skeletal muscle hypertrophy in wild-type mice [ 214 ] and attenuates, either by itself or in combination with exercise training, the skeletal muscle atrophy induced in different disease animal models [ 215 , 216 , 217 , 218 ], including DMD [ 219 ]. In mdx mice, it also reduces skeletal muscle necrosis and the expression of inflammatory markers [ 214 ].…”
Section: Pharmacological Therapies For Mds: Fight Os Inflammation And...mentioning
confidence: 99%
“…This polyphenol further promotes skeletal muscle hypertrophy in wild-type mice [ 214 ] and attenuates, either by itself or in combination with exercise training, the skeletal muscle atrophy induced in different disease animal models [ 215 , 216 , 217 , 218 ], including DMD [ 219 ]. In mdx mice, it also reduces skeletal muscle necrosis and the expression of inflammatory markers [ 214 ]. As evaluated in a pilot randomized controlled trial in senior adults, it enhances the aerobic capacity and improves skeletal muscle mitochondrial function in combination with exercise [ 220 ].…”
Section: Pharmacological Therapies For Mds: Fight Os Inflammation And...mentioning
confidence: 99%
See 1 more Smart Citation
“…One such condition is Duchenne muscular dystrophy (DMD), a progressive and fatal neuromuscular disorder with no cure. Woodman et al [ 12 ] treated mdx mice with a low dose of resveratrol (5 mg/kg body weight/day) for 15 weeks. The study found resveratrol to reduce exercise-induced muscle necrosis in dystrophic muscle and lower gene expression of immune cell markers cluster of differentiation (CD) 86 and CD163.…”
mentioning
confidence: 99%